Validity and responsiveness of the work functioning impairment scale (WFun) in workers with pain due to musculoskeletal disorders - Makishima, Misako (J Occup Health, 2017)
OBJECTIVE: To determine the convergent validity and responsiveness of the work functioning impairment scale (WFun) in workers with musculoskeletal disorder-related pain. METHODS: Participants were extracted from an internet user study and prospectively examined using the pain intensity numerical rating scale (pain-NRS), the work ability numerical rating scale (productivity-NRS), and the WFun at baseline, 2 weeks, 6 weeks, and 3 months. The convergent validity and responsiveness of the WFun were examined by multilevel regression analysis. RESULTS: A total of 786 workers participated and 593 completed all surveys. The WFun score gradually increased and decreased as the pain-NRS and the productivity-NRS increased, respectively. Changes in the WFun score steadily increased and decreased as changes in the pain-NRS and the productivity-NRS increased, respectively. Multilevel analyses showed that all linear associations were significant. CONCLUSIONS: The convergent validity and responsiveness of the WFun were consistent with the expected direction and magnitude.